2019
DOI: 10.1089/lap.2018.0293
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Radiofrequency Ablation of Myomas: Technique, Outcomes, and Complications

Abstract: TRFAM is an effective and safe technique in selected patients for the treatment of metrorrhagia secondary to myomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The mean reduction in fibroid volume was 41% at the end of 3 months with a 25 mg dose of mifepristone, which is comparable to previous studies [11][12][13][14]. In previous studies, the one-year uterine volume reduction rate of RFA ranged from 60% to 90% [2][3][4][5][6][7][8][9][10]. Our results are within the previously reported ranges.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The mean reduction in fibroid volume was 41% at the end of 3 months with a 25 mg dose of mifepristone, which is comparable to previous studies [11][12][13][14]. In previous studies, the one-year uterine volume reduction rate of RFA ranged from 60% to 90% [2][3][4][5][6][7][8][9][10]. Our results are within the previously reported ranges.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, ultrasound-guided (US-guided) radiofrequency ablation (RFA) has been the focus of interest as a minimally invasive strategy for patients with symptomatic uterine fibroids. Previous studies have reported that RFA can provide symptomatic relief and significant improvement in the quality of life [2][3][4][5][6][7][8][9][10]. However, optimal patients might be those with small fibroids (diameter <5 cm or volume < 180 cm 3 ) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lim et al 5 reported that laparoscopic Bongers et al 15 39 -23 -4.4 -3.1 -Brölmann et al 16 Garza-Leal 17 ----Braun et al 18 114 -60 6.8 -3.2 --Brucker et al 19 66 -24 10.0 -5.5 20.5 (5, 103) a 10.0 (2, 86) a Hahn et al 20 Krämer et al 21 Carrafiello et al 22 20 (15, 25) b ---Cho et al 23 -(10, 40) ---Cho et al 24 ----Chudnoff et al 25 126 -60 -9.0 (2, 60) a 5.0 (0, 29) a Galen et al 26 Guido et al 27 Berman et al 28 Chudnoff et al 29 47 -30 2. 30 Galen et al 31 140 (42, 290) a -4.5 (1, 11) b 4.0 (2, 10) a Garza-Leal et al 32 Robles et al 33 Ghezzi et al 34 25 (20, 45) a 18 c --Bergamini et al 35 Iversen and Dueholm 36 ----Iversen et al 37 Jiang et al 38 25 (20, 30) b ---Kim et al 39 18 -5 ---Lee et al 40 ----Marcos et al 41 36 -11 12.0 (8, 24) b --Meng et al 42 ----Rattray et al 43 73 -26 6.7 -3.0 -11.1 -7.6 Rey et al 44 17 (11, 44) b ---Turtulici et al 45 28 (16, 43) b ---Wu et al 46 -(20, 40) 2.5 c --…”
Section: Discussionmentioning
confidence: 99%